DESIGN & DEVELOPMENT OF GLIPIZIDE FAST DISSOLVING TABLETS USING NATURAL GUM SUPERDISINTEGRANT - Nagajyothi, Bandaru; Babu, M.Kishore (Asian Journal of Pharmaceutical and Clinical Research, 2014)
The motive of this research work was to develop fast dissolving tablets of Glipizide by using fenugreek gum as a natural super disintegrating agent which also possessed anti diabetic property for rapid control over abnormal blood glucose levels. For obtaining the fenugreek gum an attempt was made to extract it from fenugreek seeds and subjected to various physicochemical studies. Some of the physical properties such as viscosity and swelling index were found to be 293 cps and 221 respectively. Direct compression technique was employed for formulation of fast dissolving tablets of Glipizide by varying the concentrations of fenugreek gum which acted as natural super disintegrant for optimization. The formulated fast dissolving tablets were subjected to various evaluation studies. The weight variation was well within the accepted limits. Thickness and hardness of the formulated tablets were between 4.3 to 5.5 kg/cm2 and 4.9 to 5.2 mm respectively. Wetting time of the tablets was found to be between 16 to 50 sec, with water absorption ratio ranging between73.2 to 94.38percent. Invitro disintegration time of the tablets varied from 19 to 55 sec. of all the formulations, the formulation (F3) with the fenugreek gum of 5percent showed higher drug release of 95percent at the end of 25 min. further when composed with the renewed synthetic super disintegrants such as sodium starch glycolate (5percent), croscarmellose sodium (5percent) the release profiles of the F3 with fenugreek gum 5percent was found to be superior in terms of release and mechanisms. The influence of the drug Glipizide and Fenugreek gum formulations on the anti-diabetic activity was evaluated using glucose induced model of experimental rats. The results suggested that the fenugreek gum showed a promising anti diabetic activity with Glipizide. KEY WORDS: Glipizide, Fenugreek gum, Fast dissolving tablets, Additive Antibiotic activity